1984
DOI: 10.1037/0012-1649.20.4.584
|View full text |Cite
|
Sign up to set email alerts
|

"Merds that laugh don't like mushrooms": Evidence for deductive reasoning by preschoolers.

Abstract: The study examines the relationship between the development of logical processes required in deductive reasoning and their ocmsions of use. Verbal syllogism problems were presented to 4-to 5-year-old children. The problems were systematically varied in content (fantasy premises; premises incongruent with real-world events; premises congruent with real-world events), form, and order of presentation of problem types. Results indicate that young children are capable of making deductive inferences required in solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
119
1
5

Year Published

1990
1990
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(129 citation statements)
references
References 17 publications
4
119
1
5
Order By: Relevance
“…Indeed, within a Piagetian framework, the ability to draw deductive inferences is seen as requiring (at a minimum) concrete operations (Gellatly, 1987). Thus, a study by Hawkins et al (1984) produced some very surprising results. Hawkins et al (1984) gave 4-and 5-year-old children a number of verbal syllogisms (e.g., "Pogs wear blue boots.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, within a Piagetian framework, the ability to draw deductive inferences is seen as requiring (at a minimum) concrete operations (Gellatly, 1987). Thus, a study by Hawkins et al (1984) produced some very surprising results. Hawkins et al (1984) gave 4-and 5-year-old children a number of verbal syllogisms (e.g., "Pogs wear blue boots.…”
mentioning
confidence: 99%
“…''); and others, called fantasy problems, contained premises describing mythical creatures foreign to practical knowledge, as in the pogs example above. Hawkins et al (1984) found that children performed best on congruent problems (averaging about 94% correct responses), and worst on incongruent problems (averaging about 13% correct responses), with intermediate performance on fantasy problems (averaging 73% correct responses). Performance on the fantasy problems was taken as most indicative of reasoning ability because these problems necessarily prevented children from answering on the basis of preexisting empirical knowledge.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that children, even those as young as preschool age, can draw deductively valid conclusions (e.g., Dias & Harris, 1988Hawkins, Pea, Glick, & Scribner, 1984). However, other studies have found that both adults (e.g., Evans, Newstead, & Byrne, 1993;Johnson-Laird & Byrne, 1991;Newstead & Evans, 1995;Wason & Johnson-Laird, 1972;Woodworth & Sells, 1935) and children (e.g., Galotti & Komatsu, 1989;Kuhn, 1989;Markovits, 1993;Markovits, Schleifer, & Fortier, 1989;Ward & Overton, 1990) make frequent logical errors when reasoning deductively.…”
Section: Deductive Reasoningmentioning
confidence: 89%
“…Available evidence does not support the view that proper deductive reasoning suddenly appears at any particular point in development. In fact, there is substantial evidence that preschool children routinely reach appropriate conclusions from various combinations of premises (Braine, 1990;Braine and Rumain, 1983;Hawkins et al, 1984;Markovits et al, 1989;Thayer & Collyer, 1978) and that even adults typically fail to reach appropriate conclusions for a variety of complex logical problems (Evans, 1982(Evans, , 1983Wason and Johnson-Laird, 1972).…”
Section: The Development Of Rationalitymentioning
confidence: 99%